CEO power dynamics and firms' reported earnings quality in Egypt: Moderating role of corporate governance - Dalia Ali Mostafa Hemdan; Suhaily Hasnan; Saif Ur Rehman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
This study aims to explore the factors that influence the firm's reported earnings quality (FREQ) for a sample of Egyptian firms from 2008 to 2019 by using panel data. The findings show that CEO power dynamics (CEO duality, CEO ownership, CEO tenure and CEO political connections) as negative determinants of FREQ in Egypt. Further, we investigate the role of corporate governance as weakening or substitution mechanism. We find that board independence serves as weakening mechanism for negative association between CEO ownership and CEO tenure, and FREQ. In contrast, the findings do not hold for weakening or substitution role of board independence between CEO duality and CEO political connection, FREQ. The findings also support maxim of tokenism as role of gender diversity is insignificant. Importantly, we find the presence of gender critical mass serves as substitution mechanism for negative association between CEO power dynamics (CEO duality, CEO ownership, CEO tenure and CEO political connections) and FREQ. Finally, we observed robustness in our main analyses for propensity matching score and differencein-difference techniques. The study has a novel contribution in existing research since it highlights the role of CEO power dynamic in an emerging economy and further provides an insight to the role of corporate governance.
Keywords: 330; CEO power dynamics; corporate governance; firms' reported earnings quality; CEO tenure; CEO ownership; Egypt